Evaluation of antiarrhythmic and cardioprotective properties of some 8-aminosubstituted of 7-β-hydroxy-γ-m-ethylphenoxypropylxanthine - Samura, I. B.; Ngene, Ch. B.; Yousfi, K.; Darah, C.; Самура, Ірина Борисівна (Запорізький державний медичний університет, 2019)
Despite huge improvements in cardiovascular care and the decline in cardiovascular deaths over the past several decades due to improved preventative strategies, the incidence of sudden cardiac death (SCD) as a proportion of overall cardiovascular deaths has increased. SCD and arrhythmias continue to represent a major international public health problem and is still the biggest killer worldwide, accounting for 17 million deaths every year with sudden cardiac death accounting for 25 % of these. Development of new effective and devoid of side effects antiarrhythmic drugs (AADs) remains an actual problem of modern pharmacology. The purpose of this research was to investigate the antiarrhythmic properties and effect on circulatory system of some new synthesized 8-aminosubstituted of 7-β-hydroxy-γ-m-ethylphenoxypropylxanthines. Materials and methods. The study was carried out on mature white nonlinear male rats weighing 170-210 g collected from the breeding center of Institute of Pharmacology and Toxicology of the Academy of Medical Sciences of Ukraine. The control and study groups consisted of 7 animals each. Some newly synthesized compounds in a series of 8-aminosubstituted of 7-β-hydroxy-γ-m-ethylphenoxy-propylxanthine (compounds 1-10) synthesized by Professor Romanenko M.I. at the Department of Biological Chemistry (the head of Department, Professor Alexandrova K.V.) of Zaporozhye State Medical University were the object of the research. The LD50 of investigated compounds were calculated according to the method of Litchfield and Wilcoxon with application 2. The determination of antiarrhythmic activity of compounds studied was performed using an intravenous injection. Arrhythmias were evoked in rats anesthetized with sodium thiopental (40mg/kg, ip) by a single iv injection of calcium chloride at a dose of 250 mg/kg, adrenaline hydrochloride 0.3mg/kg, or aconitine (40 mcg/kg), in a volume of 1 mL/kg. As reference drugs Procainamide and Ajmaline were injected once intravenously at a dose of 20 mg/kg and 2 mg/kg respectively. Electrocardiographic studies were carried out on EEGP4-02 apparatus using second standard (bipolar extremity) lead at a tape speed of 50 mm/s within10 min. The frequency of supraventricular and ventricular arrhythmias were calculated in each group.
Keywords: тези доповідей